1951
DOI: 10.1139/p51-005
|View full text |Cite
|
Sign up to set email alerts
|

The Scattering Lengths of the Deuteron

Abstract: The angular variation of the scattering of neutrons of 0.0724 ev. energy by deuterium gas has been measured. Comparison with theoretical calculations of this variation gives a ratio of scattering lengths:[Formula: see text]In combination with the known total scattering cross section of the free deuteron of 3.44 ± 0.06 barns this gives for the scattering lengths the two sets of values:[Formula: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1957
1957
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…7 shows, the present measurements are in very good agreement (except perhaps at the largest angle) with the calculated CG(obs) curves at all energies. The S-wave phases used in the calculation are consistent with one of two sets of experimental zeroenergy n-d scattering lengths, 43 namely, the quartet length 4 a= (6.4zb0.3)XlO~1 3 cm and the doublet length 2 #=(0.7±0.3)X10~1 3 cm. These experimental values (at least the value of 4 a) are in good agreement, furthermore, with n-d zero-energy scattering lengths derived from the p-d scattering lengths; and the latter in turn were consistent with the p-d phase-shift analysis described above.…”
Section: B Differential Cross Sectionsupporting
confidence: 65%
“…7 shows, the present measurements are in very good agreement (except perhaps at the largest angle) with the calculated CG(obs) curves at all energies. The S-wave phases used in the calculation are consistent with one of two sets of experimental zeroenergy n-d scattering lengths, 43 namely, the quartet length 4 a= (6.4zb0.3)XlO~1 3 cm and the doublet length 2 #=(0.7±0.3)X10~1 3 cm. These experimental values (at least the value of 4 a) are in good agreement, furthermore, with n-d zero-energy scattering lengths derived from the p-d scattering lengths; and the latter in turn were consistent with the p-d phase-shift analysis described above.…”
Section: B Differential Cross Sectionsupporting
confidence: 65%
“…With these overlapping datasets, the ν(q) dispersion relation was plotted for the [ζ00], [ζζ0], and [ζζζ] directions. The data showed that the phonon intensities were largest near the reciprocal lattice points varying such as kT/ν 2 at relatively high temperatures, as given by Equations (11) and (12).…”
Section: Figurementioning
confidence: 91%
“…Two accounts of measurements of the neutron scattering lengths of the two spin states of the deuteron were given [11,12] in 1950 and 1951, and in this case, the interest was on the impact on the theory of nuclear forces rather than the atomic physics of the molecule. First, 1.063 Å neutrons from the NRX reactor were selected by reflection from the (100) planes of NaCl and were scattered by D2 molecules at 30 atmospheres and 77.4 • K and counted in a BF3 counter.…”
Section: Nuclear Physics and The Consequences For Inelastic Scatteringmentioning
confidence: 99%
“…Ifwe put on this plot the new (E T = --8.48 MeV, 2a = 0.15• fin [3]) and the old (E T = --8.48 MeV, 2a --~ 0.7• fm [4]) experimental points, it turns out that the PHILLIPS line goes through the old experimental point. If we accept the new experimental point, we are faced with the task of finding such features of the interaction between nucleons which, in a theoretical calculation, would lead us to the new experimental point, i.e.…”
mentioning
confidence: 98%